Psychotherapy : Practice, Research, Policy - Edited by VandenBos, Gary R. (London Sage Publications, 1980)
Sage Studies in Community Mental Health is a book series consisting of both single-authored and co-authored monographs and concisely edited collections of original articles which deal with issues and themes of current concern in the community mental health and related fields. Drawing from research in a variety of disciplines, the series seeks to link the work of the scholar and practitioner in this field, as well as advance current knowledge in community mental health.
Include Graphs and Tables
Keywords: Psychotherapy -- Psychotherapy--Evaluation -- Psychotherapy--Research